Chromatin organization and transcriptional control of gene expression in Drosophila. - Farkas, G.; Leibovitch, B.A.; Elgin, S.C. (Gene, 2000)
It is increasingly clear that the packaging of DNA in nucleosome arrays serves not only to constrain the genome within the nucleus, but also to encode information concerning the activity state of the gene. Packaging limits the accessibility of many regulatory DNA sequence elements and is functionally significant in the control of transcription, replication, repair and recombination. Here, we review studies of the heat-shock genes, illustrating the formation of a specific nucleosome array at an activatable promoter, and describe present information on the roles of DNA-binding factors and energy-dependent chromatin remodeling machines in facilitating assembly of an appropriate structure. Epigenetic maintenance of the activity state within large domains appears to be a key mechanism in regulating homeotic genes during development; recent advances indicate that chromatin structural organization is a critical parameter. The ability to utilize genetic, biochemical and cytological approaches makes Drosophila an ideal organism for studies of the role of chromatin structure in the regulation of gene expression.